Les étudiants en formation à l’enseignement professionnel au Québec : portrait d’un groupe particulier d’étudiants universitaires - Balleux, André (Canadian Journal of Higher Education, 2006)
Registration in a university training program for teachers of vocational training represents a major transition characterized by a progressive rupture between practice of a trade and practice as a teacher. This situation particular to Quebec teachers of vocational training makes them unique students, with characteristics and profiles different from their colleagues of the general sector. This article presents the results of a study conducted with students enrolled in training programs for teaching vocational training at Sherbrooke University aimed at building a first portrait of this characteristic group. This research constitutes the first step in a process which will contribute to a better understanding of the identity, the problems and the peculiar situation of teachers of vocational training at their moment of transition between practice of a trade and teaching their trade.